3D Nanolithography via Holographic Multi‐Focus Metalens (Laser Photonics Rev. 18(11)/2024) - Wang, Xinger; Fan, Xuhao; Liu, Yuncheng; Xu, Ke; Zhou, Yining; Zhang, Zexu; Chen, Fayu; Yu, Xuan; Deng, Leimin; Gao, Hui; Xiong, Wei (Laser & photonics reviews, 2024)
3D Nanolithography via Holographic Multi‐Focus Metalens In article number 2400181, Xinger Wang, Hui Gao, Wei Xiong, and co‐workers propose a metasurface‐based two‐photon polymerization technique. A metasurface is introduced into 3D nanolithography for the first time, resulting in the construction of a miniaturized and simplified two‐photon lithography system that achieves efficient multi‐focus parallel processing with high uniformity. It is believed that the utilization of the metasurface will provide a novel two‐photon lithography operating platform, enabling richer and more flexible printing functionalities while maintaining system miniaturization and low cost.